Growing Old and Being Gay or Lesbian in Malta: Anticipating Care in a Heteronormative Society - Vella, Christian (Magyar Gerontológia, 2025)
Malta presents a unique paradox for sexual minority elders: it boasts some of the world’s most progressive LGBTIQ+ legislation, yet retains a deeply rooted, religiously conservative social fabric. This article explores how this paradox shapes the ageing experiences and anticipated care needs of older gay men and lesbian women. Drawing on critical gerontology and utilising the Biographic-Narrative Interpretive Method (BNIM), to collect the data, using Thematic Analysis this study examins the life histories of participants aged 58 to 72. Findings reveal a pervasive fear of ‘re-closeting’ upon entry into long-term care, driven by a lifetime of navigating heteronormativity. A distinct gendered divergence emerged: while male participants largely embraced a gay identity, female participants frequently rejected the ‘lesbian’ label, adopting strategies of protective silence. The study challenges normative models of ‘successful ageing,’ highlighting instead the resilience found in ‘families of choice.’ The article concludes that despite legal equality, the lack of culturally competent care creates a precarious future for Maltese sexual minorities, necessitating urgent policy interventions and affirmative staff training to support ageing in place.